The Paradigm of Religious Moderation: A Sociological Perspective from Karl Mannheim and Its Significance for National Commitment - Winarto, Winarto; Wawaysadhya, Wawaysadhya; Taufiq, Thiyas Tono (FIKRAH, 2024)
Conflict based on religious and belief differences is one of the longstanding SARA (ethnicity, religion, race, and inter-group relations) issues that persist to this day. Yet, all religions and beliefs come with noble teachings and bring messages of peace for all creation. The paradigm of religious moderation emerged as a perceived solution to various religion-motivated conflicts. This study aims to investigate whether religious moderation presented by policymakers and academics constitutes objective knowledge from Karl Mannheim's perspective and its relevance to strengthening national commitment. This research falls into the category of library research. The methodology employed is qualitative with philosophical and sociological approaches. The findings of this study are: First, moderate Islamic theology refers to the ideas and attitudes of believers who have a balanced and non-extremist view characterized by tawassuth (moderation), tawazun (balance), i'tidal (upright and firm), tasamuh (tolerance), and musawah (egalitarianism and non-discrimination). Second, the emergence of moderate Islamic theology is due to the socio-cultural conditions of society, security conditions, and academic reasons. Third, Mannheim's three types of meanings: Objective meaning, the government's response, and academics' perspectives are objective actions considering the contemporary social context that develops narratives of intolerance and radicalism. Expressive meaning, the narrative of moderate Islamic theology is also an expression of the actors or formulators of the moderate Islamic theology concept. Documentary, it means these actors are recorded in history as part of culture. Its relevance shows that the presence of moderate Islamic theology is needed to strengthen the commitment to the nation's four pillars. The recommendation from this research is that it can be used to strengthen the argument for national commitment through the philosophical concept of moderate Islam.